Temporal Lensing: An Interactive and Scalable Technique for Web3D/WebXR Applications in Cultural Heritage - Fanini, Bruno; Ferdani, Daniele; Demetrescu, Emanuel (Heritage, 2021)
Today, Web3D technologies and the rise of new standards, combined with faster browsers and better hardware integration, allow the creation of engaging and interactive web applications that target the field of cultural heritage. Functional, accessible, and expressive approaches to discovering the past starting from the present (or vice-versa) are generally a strong requirement. Cultural heritage artifacts, decorated walls, etc. can be considered as palimpsests with a stratification of different actions over time (modifications, restorations, or even reconstruction of the original artifact). The details of such an articulated cultural record can be difficult to distinguish and communicate visually, while entire archaeological sites often exhibit profound changes in terms of shape and function due to human activities over time. The web offers an incredible opportunity to present and communicate enriched 3D content using common web browsers, although it raises additional challenges. We present an interactive 4D technique called “Temporal Lensing”, which is suitable for online multi-temporal virtual environments and offers an expressive, accessible, and effective way to locally peek into the past (or into the future) by targeting interactive Web3D applications, including those leveraging recent standards, such as WebXR (immersive VR on the web). This technique extends previous approaches and presents different contributions, including (1) a volumetric, temporal, and interactive lens approach; (2) complete decoupling of the involved 3D representations from the runtime perspective; (3) a wide range applications in terms of size (from small artifacts to entire archaeological sites); (4) cross-device scalability of the interaction model (mobile devices, multi-touch screens, kiosks, and immersive VR); and (5) simplicity of use. We implemented and developed the described technique on top of an open-source framework for interactive 3D presentation of CH content on the web. We show and discuss applications and results related to three case studies, as well as integrations of the temporal lensing with different input interfaces for dynamically interacting with its parameters. We also assessed the technique within a public event where a remote web application was deployed on tablets and smartphones, without any installation required by visitors. We discuss the implications of temporal lensing, its scalability from small to large virtual contexts, and its versatility for a wide range of interactive 3D applications.